Meninjau Ulang Dekonstruksi Konsep Aurat Wanita Dalam Teori Batas Ala Muhammad Syahrur - Auliya, Sefri; Gazali, Hidayatul Azizah (Universitas Islam Negeri Imam Bonjol Padang, 2020)
Muhammad Syahrur is one of the figures who is concerned in the issue of female Aurat. Although his presence is very controversial, but he still tries to formulate his own concept. According to him, Allah SWT has set the period of Aurat concept since the time of the Prophet Adam and Eve. In fact, for him the measurement of Aurat is ashame and has nothing to do with halal and haram. Through the Theory of boundary, Syahrur sets minimum and maximum limits to deconstruct the concept of females’ Aurat. However, this method is considered wrong because it is to eliminate the sacredity of religious texts and contradict with the opinions among majority of scholars.